Career Aspirations and Emotional Adjustment of Chinese International Graduate Students. (18th December 2015) - Cozart, Deanna L.; Rojewski, Jay W.
There are more Chinese student-scholars than any other group of international students studying in the United States. Despite this, there are relatively few studies that have focused on specific educational needs and required career support services for Chinese international students. This exploratory study was conducted to determine the relationship between career aspirations and emotional adjustment of Chinese international students. Results from Chinese students were compared with those of students from the United States. Relationships between the career aspirations and emotional adjustment of Chinese and U.S. students did not reveal statistically significant differences. However, regression analysis indicated that social stress was a statistically significant predictor of career aspirations for U.S. students. Chinese and U.S. students were more alike than different on career aspirations and emotional adjustment, and observed educational similarities appeared to outweigh any cultural differences that existed when determining these outcomes.